Osteosynthesis of Neck of Femur Fracture below 65 years of Age: does timing of surgery influence osteonecrosis, nonunion and functional outcome? - Thapa, J.; Shrestha, D.; Kayastha, S. R.; Dhoju, D.; Shrestha, R.; Sharma, R.; Regmi, R. (Kathmandu University Medical Journal, 2021)
Background Influence of timing of injury surgery interval in outcome of osteosynthesis of neck of femur has always been a matter of debate. Patients in our set up have been surgically treated for neck of femur fracture with wide range of injury surgery interval which could have resulted in varied functional outcome and radiological outcome. Objective To evaluate the difference in functional outcome, femoral head osteonecrosis and non-union in fracture neck of femur fixed within and after twenty-four hours. Method All patients, who had undergone osteosynthesis for the neck of femur fractures via open or closed technique from 2010 to 2018 were analyzed retrospectively. The cases were examined and evaluated in terms of injury surgery interval, fracture union, functional status using Modified Harris Hip Score, complications like femoral head osteonecrosis and non-union. Result Fifty patients with an average injury surgery interval of 34±28 hours were evaluated. Twenty three (46%) cases were included in early surgery group (< 24 hours) and 27 (54%) patients were included in delayed (> 24 hours) surgery group. Incidence of femoral head osteonecrosis was reported in two (4%) cases, both being in delayed fixation group (p=0.49). Non-union was reported in four (8%) patients, one in early fixation group and three in delayed fixation group (p=0.61). The average Modified Harris Hip Score in early fixation group was 87 and in delayed fixation group was 84 (p=0.1). Forty two (84%) cases had a good quality of reduction and eight (16%) had a poor reduction. Non-union and functional outcome significantly differed between the good and poor reduction group (p=0.001 and 0.004 respectively). Conclusion There is no significant difference in the functional and radiological outcome of cases operated before and after 24 hours for osteosynthesis of neck of femur fractures in patients 16 to 65 years age group. However, poor reduction is significantly associated with the increased rate of non-union and poor functional outcome.